EU Partners benefit from Germany's US export success - Manuel Fritsch; Galina Kolev; Jürgen Matthes (Institut der deutschen Wirtschaft (IW), 2017)
In the debate of the US current account deficit, Donald Trump focuses his criticism to a large extent on Germany. But in the case of a trade war it would not affect Germany alone. Due to intermediate input linkages, hundreds of thousands of jobs in the EU partner countries depend on the success of German exports to the US.
Keywords: 330